2003
DOI: 10.4049/jimmunol.170.8.4196
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Retention of the MHC Class I-Related Chain B Ligand of NKG2D by the Human Cytomegalovirus UL16 Glycoprotein

Abstract: Infection by human CMV induces expression of the cellular MHC class I-related chain A (MICA) and chain B (MICB) surface proteins, which function as ligands for the activating NKG2D receptor. Engagement of NKG2D triggers NK cells and costimulates Ag-specific effector CD8 αβ T cells. The potency of MHC class I-related chain-NKG2D in stimulating these anti-viral immune responses may be countered by a CMV-encoded transmembrane glycoprotein, UL16, which specifically binds MICB as well as two of the UL16-binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 20 publications
3
89
0
Order By: Relevance
“…tivity of NKG2D ligand recognition is important in several biological settings, such as immune evasion by viral pathogens and tumor cells. Immune responses mediated by NK cells and CD8 T cells are important in the control of cytomegalovirus (CMV), and human and murine CMV encode viral proteins (UL16 for human CMV and gp40 for murine CMV) that retain NKG2D ligands in intracellular compartments and thus impair antiviral NK cell and CD8 T cell responses (35)(36)(37)(38). Recognition of tumor cells that express NKG2D ligands can be impaired by tumor-derived soluble MICA, which reduces NKG2D surface expression on tumor-infiltrating and circulating T cells (19,39).…”
Section: Discussionmentioning
confidence: 99%
“…tivity of NKG2D ligand recognition is important in several biological settings, such as immune evasion by viral pathogens and tumor cells. Immune responses mediated by NK cells and CD8 T cells are important in the control of cytomegalovirus (CMV), and human and murine CMV encode viral proteins (UL16 for human CMV and gp40 for murine CMV) that retain NKG2D ligands in intracellular compartments and thus impair antiviral NK cell and CD8 T cell responses (35)(36)(37)(38). Recognition of tumor cells that express NKG2D ligands can be impaired by tumor-derived soluble MICA, which reduces NKG2D surface expression on tumor-infiltrating and circulating T cells (19,39).…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous ligands for human NKG2D are MHC class I chain-related proteins (MIC)A and MICB and another family of class I-related molecules, the UL16-binding proteins (ULBP)1-3. Some NKG2D ligands are up-regulated in cells infected with CMV (47,48), but the signals regulating the expression of MIC and ULBP in the context of other viral infections have yet to be defined.…”
Section: Nkp46 and Nkg2d Recognition Of Infected Dendritic Cells Is Nmentioning
confidence: 99%
“…Down-regulation of NKG2DL on Ma-Mel-86b cells was dependent on the concentration of IFN-g, as shown in Figure 2c, with 20 U/ml being already sufficient to induce a clearly detectable reduction in MICA and ULBP2 expression levels. We speculated that upon IFN-g treatment NKG2DL might be sequestered to distinct cellular compartments as observed during infections [30][31][32] or retained intracellular as reported for tumors, including melanoma. 18,33 However, Western blot analysis revealed that in the presence of IFN-g, MICA and ULBP2 molecules were not retained within Ma-Mel-86b cells rather the specific cellular protein levels were decreased strongly after 48 hr of cytokine treatment (Fig.…”
Section: Nkg2dl Surface Expression On Melanoma Cells Is Decreased In mentioning
confidence: 99%